In Vitro Antioxidant, Anti-Inflammatory and Skin Permeation of Myrsine africana and Its Isolated Compound Myrsinoside B - Fibrich, Bianca; Gao, Xinyi; Puri, Ashana; Banga, Ajay K.; Lall, Namrita (Frontiers in Pharmacology, 2020)
Dermal aging is characterized by states of oxidative stress, chronic inflammation, and abnormal proteolytic degradation due to the action of hydrogen peroxide, superoxide, 5-lipoxygenase, and elastase respectively. Noteworthy elastase inhibition has previously been reported, and so this study aimed to investigate the ability of M. africana and myrsinoside B to reduce the activity of hydrogen peroxide, superoxide and 5-lipoxygenase as supplementary mechanisms of action by which M. africana may reduce the appearance of wrinkles. The use of maltose microneedles were also investigated as a means to enhance the delivery of myrsinoside B into the skin as this is a crucial aspect to investigate when characterizing the efficacy of an active ingredient . Myrsine africana has traditionally been used for skin allergies, boils, and to purify blood (as an astringent) and was selected for this study based on it use in skincare. The crude extract exhibited IC50’s of 56.08 ± 2.88 µg/mL and 132.74 ± 1.64 µg/mL against the hydrogen peroxide and superoxide radicals, while myrsinoside B exhibited IC50’s of 52.19 ± 4.16 µg/mL and 192.14 ± 3.52 µg/mL respectively. The IC50 of the extract and compound against 5-lipoxygenase was 29.65 ± 2.92 µg/mL and 29.33 ± 3.08 µg/mL, respectively. No toxicity was observed in vitro at the highest concentration tested. Microneedle treatment increased the permeation of the active through the skin after 24 h to 12.46  5.14 µg/cm2 compared to the passive group (1.30 0.85 µg/cm2). The amount of active retained in the epidermis and dermis was 8.97 ± 0.90 µg/cm2 and 6.98 ± 0.73 µg/cm2 respectively, greater than the retention observed in the passive group (3.24 ± 1.41 µg/cm2 and 3.27 ± 1.47 µg/cm2, respectively). Myrsine africana and myrsinoside B showed promising antioxidant and anti-inflammatory activity thus supporting the potential of Myrsine africana and myrsinoside B as anti-wrinkle agents. Further, treatment of dermatomed human skin with maltose microneedles facilitated topical delivery of myrsinoside B and provided an effective means for compound delivery to ensure maximum effect.